Proposing Performance Review Method to Improve Employee Productivity in PT MAPI - Fitri, Astrid Iryana; Lantu, Donald Crestofel (Trunojoyo University of Madura, 2023)
Objectives of this study are to find the employee and management perception related to the employee productivity in PT MAPI and how impactful the employee performance review that produces an annual reward to the level of employee productivity at work, and to develop current performance review method which will be used in the future to boost employee productivity. The author use qualitative techniques to gather information from relevant stakeholders, from HRGA staff and related managers. The study found that of the qualitative interview, it provides insight to the company that the existing performance review method still has many deficiencies that need improvement in terms of preparation and implementation and monitoring of the follow-up results of the performance review. In order to address issues with the performance review process currently being used by the company, PT MAPI must review the current process so that improvements can be made from changes to the performance review process, which, based on the results of the interviews, will impact employee productivity.